Analisis Hubungan Karakteristik Sosial Ekonomi Pembudidaya Terhadap Produktivitas Budidaya Ikan Hias di Kota Cimahi - Vira Azhari Yulisa; Asep Agus Handaka; Ujang Subhan; Atikah Nurhayati (Jurnal Galung Tropika, 2025)
Cimahi City is one of the administrative areas in West Java with the potential for ornamental fish production businesses. Increasing ornamental fish productivity is necessary to increase income and the community's economy in Cimahi City. This study aims to describe the socio-economic characteristics and profiles of fish farmers and to analyze the socio-economic correlation of farmers to the level of productivity of ornamental fish farming businesses. This study uses a survey method by administering questionnaires as a data collection tool. The data obtained were tabulated and analyzed using the Spearman Rank Correlation test with the help of software in the form of SPSS version 23 for Windows. The social and economic parameters observed were age, gender, education, experience, social organization, and income. The results of the correlation analysis showed that the experience variable and the social organization variable influenced productivity. Experience and social organization have a positive relationship direction with a moderate category on productivity with values ??of 0.462 and 0.373. Thus, farmers' high experience and social organization will impact the productivity of ornamental fish farming businesses.